Desempenho de nanomateriais na degradação fotocatalítica da Rodamina B sob radiação solar - Matos, Andrezza Pereira de (2024)
This study investigated the efficiency of various nanomaterials in the degradation of Rhodamine B dye, using metal oxides and ferrites as photocatalytic catalysts. Initially, desirability analysis and experiments with calcium ferrites showed low efficiency, leading to the inclusion of other catalysts such as zinc, calcium, copper, bismuth oxides, and barium and zinc-barium ferrites. Zinc oxide emerged as the most effective nanomaterial, achieving up to 84.12% efficiency under optimized conditions, due to its ability to absorb UV radiation and generate reactive oxygen species. Zinc-barium ferrite exhibited an efficiency ranging from 32.64% to 39.17%, outperforming barium ferrite. The heterojunction between ferrites and metal oxides was optimized using Central Composite Design within Response Surface Methodology, revealing that pH had a significant impact on efficiency, while hydrogen peroxide concentration and catalyst mass had no significant effects. The ideal solution identified to maximize efficiency included a heterojunction proportion of 0.08 g/L and a pH of 3.73. This research contributes to the Sustainable Development Goals (SDGs) by improving water quality (SDG 6), promoting technological innovation (SDG 9), utilizing responsible processes (SDG 12), harnessing solar energy (SDG 13), and protecting ecosystems (SDG 15). This work advances the science of photocatalysis and supports global goals for sustainable development.